Plausible mechanisms for brain structural and size changes in human evolution - Blazek, Vladimir; Brùzek, Jaroslav; Casanova, Manuel F (Collegium antropologicum, 2011)
Encephalization has many contexts and implications. On one hand, it is concerned with the transformation of eating habits, social relationships and communication, cognitive skills and the mind. Along with the increase in brain size on the other hand, encephalization is connected with the creation of more complex brain structures, namely in the cerebral cortex. It is imperative to inquire into the mechanisms which are linked with brain growth and to find out which of these mechanisms allow it and determine it. There exist a number of theories for understanding human brain evolution which originate from neurological sciences. These theories are the concept of radial units, minicolumns, mirror neurons, and neurocognitive networks. Over the course of evolution, it is evident that a whole range of changes have taken place in regards to heredity. These changes include new mutations of genes in the microcephalin complex, gene duplications, gene co-expression, and genomic imprinting. This complex study of the growth and reorganization of the brain and the functioning of hereditary factors and their external influences creates an opportunity to consider the implications of cultural evolution and cognitive faculties.
Keywords: Cell Differentiation; regulace genové exprese; buněčná diferenciace; lidé; Gene Expression Regulation; biologická evoluce; Biological Evolution; Brain; Gene Duplication; duplikace genu; mozek; Humans